The Influence of Community Readiness on the Level of Digital Population Identity (DPI) Activation in Sibolga City - Hasibuan, Nur’ainun; Tiurlina Hasmawati Sihite , Tiurlina; Fitryany Daulay , Fitryany; Delita Sihotang, Delita; Hendra Saputra, Hendra (Jurnal Multidisiplin Sahombu, 2025)
Digital Population Identity (IKD) is one of the innovative programs initiated by the Ministry of Home Affairs in order to digitize population administration services. This program aims to make it easier for the public to access population identity digitally, replacing or complementing the use of physical documents such as Electronic Population Cards (KTP-el) with technology-based applications. IKD is expected to increase service efficiency, provide convenience for the public, and create a more modern and integrated population administration. Based on the Sibolga City Population Administration Implementation Report for November 2024, it was recorded that as of November, 70,404 residents of Sibolga City had recorded their KTP-el and 4,777 people or 6.78% had activated IKD. This figure is still very small when compared to the national target of 25% which was then increased again to 30% or 21,121 people. This study uses a qualitative method. This study uses a single case study method to provide an in-depth picture of the readiness of the Sibolga City community to activate IKD and can also provide detailed and contextual information about the phenomenon being studied. Based on interviews with informants who came to the Dukcapil Office, they had not received sufficient information about IKD, there was no socialization to the community even though the Dukcapil Office had conveyed information related to IKD to the Head of the Environment throughout Sibolga City, but the information was not forwarded to the community. Even so, the IKD application was not immediately accepted by many people. In fact, the IKD application was flooded with criticism from various parties. Overall, the IKD application still often experiences errors and fails to access many times. This was expressed by the community and officers, both in the service and officers in the field who had tried to use the IKD application.